1982
DOI: 10.3177/jnsv.28.343
|View full text |Cite
|
Sign up to set email alerts
|

Change in vitamin A content in tissues of rats fed on a vitamin A-free diet.

Abstract: SummaryThe effect of the feeding of a vitamin A-free diet on vitamin A metabolism was studied in rats by following changes in tissue distribution of the vitamin for 24 days. The serum level of vitamin A was maintained at a constant level until the last day of the experiment, by which time the liver reserve had declined to as low as one-seventh of its initial value. In contrast, the concentration of vitamin A in the kidney increased gradually in rats fed on a vitamin A-free diet and rose to levels higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Similar increases occur with the onset of a vitamin A deficiency (15,16). Furthermore, we have shown that the retinoid accumulation in the kidney caused by TCDD appears to be primarily an increase in the amount of retinyl esters, a consequence of elevated ACARAT activity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar increases occur with the onset of a vitamin A deficiency (15,16). Furthermore, we have shown that the retinoid accumulation in the kidney caused by TCDD appears to be primarily an increase in the amount of retinyl esters, a consequence of elevated ACARAT activity.…”
Section: Discussionsupporting
confidence: 52%
“…It has been clearly established in the literature, and demonstrated again in the experiment described herein, that a toxic dose of TCDD results in elevated levels of retinoids in the kidneys of treated animals (12,13). Similar increases occur with the onset of a vitamin A deficiency (15,16). Furthermore, we have shown that the retinoid accumulation in the kidney caused by TCDD appears to be primarily an increase in the amount of retinyl esters, a consequence of elevated ACARAT activity.…”
Section: Discussionmentioning
confidence: 80%
“…Increased renal vitamin A is an indicator of a beginning vitamin A deficiency in the rat, whereas severe deficiency is characterized by depletion of renal vitamin A (32,33). Results obtained in the present study may thus suggest that TCDD-exposed rats, despite their substantial liver and serum levels of vitamin A, behave as if they were vitamin A deficient (Table 3).…”
Section: Golden Syrian Hamstersmentioning
confidence: 50%
“…Furthermore, during VA deficiency, kidney may contain a similar retinol concentration to liver. 44 We did not anticipate that the sows would have this degree of VA deficiency and did not collect the kidneys. Future studies could investigate carcass and other organ concentrations of retinol, as well as unaccounted-for dose loss (e.g.…”
Section: Discussionmentioning
confidence: 99%